EFEKTIFITAS SEDIAAN REPELLENT STICK EKSTRAK BUAH WALAY (Meistera chinensis) TERHADAP NYAMUK Aedes sp - Nur Saadah Daud; Sapu, Yawan moses; Sri Aprilianti Idris (Jurnal Insan Farmasi Indonesia, 2023)
Repellent is a preparation used to avoid bites from insects, including the Aedes sp mosquito. Repellent sticks are applied without direct contact with the hands, unevaporate easily and can last relatively longer on the skin. One of the plants from Southeast Sulawesi, namely Walay fruit (Meistera chinensis), contains triterpenoid and flavonoid compounds which have the potential as an active substance in anti-mosquito repellant. This study aims to formulate repellent sticks of Meistera chinensis fruit extract which effective against Aedes sp. Three formula consists of 1%, 3% and 5% extracts with additional ingredients carnouba wax, cetyl alcohol, Vaseline alba, SLS, propylene glycol, span 80, tween 80, Na benzoate, BHT, eucalyptus and aquadest. The results of the physical evaluation showed the repellent had brown in color, an eucalyptus aroma, solid, homogeneous, pH of 6.8-6.9, melting temperature 60°C-62°C, applied 1x, and was not irritating. After 14 days of storage at room temperature the repellent was stable. The repellent effectiveness against Aedes sp showed that formula C with 5% extract had the highest protection power, namely 90%. The results of the ANOVA statistical analysis obtained a value of sig.0.009 (p<0.05) which shows that there are significant differences in effectiveness between treatment groups.